The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species - Hemp, Claudia; Heller, Klaus-Gerhard (Zootaxa, 2017)
Species of the genus Phlesirtes are reviewed in this paper and 16 new species described. A key is provided to the species of Phlesirtes. Among the subtribe Karniellina of Conocephalini members of the genus Phlesirtes occupy habitats of montane to afroalpine grasslands in East Africa. All recorded species produced long-lasting, trill-like calling songs, consisting of sequences of continuously repeated syllables or syllable pairs with the peak of the carrier frequency in the low ultrasound.